Hypnopressure on Breastfeeding Self Efficacy and Breast Milk Production in Breastfeeding Mothers - Diah Evawanna Anuhgera; Sembiring, Elsaria (Optimal Midwife Journal, 2024)
Breastfeeding is one of the most important factors in a baby's health. Evaluate maternal performance and provide feedback to increase breast milk production and breastfeeding self-efficacy. Hypnopressure can help breastfeeding mothers increase breast milk production and breastfeeding self-efficacy. Low self-efficacy affects new mothers' ability to maintain breastfeeding. The aim of this study was to evaluate the effect of hypnopressure on breast milk production and breastfeeding self-efficacy. The population in this study were all post partum mothers who breastfed on the first day of birth who were at the Nining Pelawati Lubuk Pakam Clinic, Deli Serdang. The intervention group received hypnopressure; the control group received standard care. Data between groups was compared for breast milk production and breastfeeding self-efficacy scores. The sampling technique used was simple random sampling with a sample of 34 respondents. The instruments for this research are the Standard Operational Procedure for Hypnopressure, an Electric Breast Pump and the Breastfeeding Self Efficacy Scale (BSES) Short Form. The data analysis used is the dependent, independent t test, Wilcoxon test and Mann Whitney test. The results of this study showed that there was a change in increasing breast milk production before and after being given hyonopressure with a mean difference of 57.58 and a p value = 0.00, thus showing an increase in breast milk production before and after the intervention. The breastfeeding self-efficacy variable shows changes before and after with a mean difference of 19.3 and a p value = 0.00. Hypnopressure increases breast milk production and breastfeeding self-efficacy in breastfeeding mothers. Hypnopressure can be effective in maintaining breastfeeding in mothers by 41.18% and increasing breast milk production by 60.05%. It is recommended that midwives apply the hypopressure method in providing the best service for mothers and babies.